2019
DOI: 10.1017/s026357471800156x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Algorithms-Based Multi-Objective Optimal Mobile Robot Trajectory Planning

Abstract: SummaryIn this research study, trajectory planning of mobile robot is accomplished using two techniques, namely, a new variant of multi-objective differential evolution (heterogeneous multi-objective differential evolution) and popular elitist non-dominated sorting genetic algorithm (NSGA-II). For this research problem, a wheeled mobile robot with differential drive is considered. A practical, feasible and optimal trajectory between two locations in the presence of obstacles is determined through the proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 26 publications
(47 reference statements)
0
28
0
1
Order By: Relevance
“…We consider general asymmetric bounds on velocity, acceleration, and jerk [18] and present a complete trajectory generation algorithm. A multiobjective differential evolution algorithm proposed in [19] is used in trajectory planning of a mobile robot. A multiobjective teaching learning-based optimization method proposed in [20] is used to achieve optimal trajectory planning of a welding robot.…”
Section: Introductionmentioning
confidence: 99%
“…We consider general asymmetric bounds on velocity, acceleration, and jerk [18] and present a complete trajectory generation algorithm. A multiobjective differential evolution algorithm proposed in [19] is used in trajectory planning of a mobile robot. A multiobjective teaching learning-based optimization method proposed in [20] is used to achieve optimal trajectory planning of a welding robot.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic algorithms are also implemented in mobile robots. Sathiya et al [14] explained a novel concept by adopting two techniques, namely multi-objective differential evolution and non-dominated sorting genetic algorithm (NSGA-II), in order to obtain a safer path by optimizing travel time and actuators effort. The ant algorithm is implemented in navigation problematics, such as Xiaoping et al [15] explained.…”
Section: Of 19mentioning
confidence: 99%
“…Genetic Algorithms [14] Normally uses the robot kinematic and dynamic parameters to optimize the path.…”
Section: Reference Advantages Weaknessmentioning
confidence: 99%
“…The non-dominated Sorting Genetic Algorithm II was modified by Ahmed and Deb [4], taking into account travel distance, safety, and path smoothness simultaneously. The follow-up studies [5][6][7][8][9] suggested multi-objective optimization-based path planning strategies. Kim and Langari [10] utilized the Analytic Hierarchy Process (AHP) to plan an optimal path of a mobile robot considering the distance to the target, collision safety, and rotation to the target under the preference of travel.…”
Section: Introductionmentioning
confidence: 99%